Knowledge Transfer and Succession Planning in The Aviation Industry: A Review of The Literature - Evelyne UWAYEZU; Hayat El ASRI (Communications of International Proceedings, 2023)
Knowledge transfer and succession planning are crucial aspects of the aviation industry to ensure continuity, safety, and efficiency. As the industry faces challenges such as an aging workforce and the need to retain critical knowledge, the implementation of effective strategies for knowledge transfer and succession planning assumes paramount importance for ensuring organizational success. However, the gap of scholarly literature addressing this critical subject matter is disappointing. This literature review aims to provide a comprehensive analysis of the current state of knowledge transfer and succession planning practices in the aviation industry and tries to cover the gap therewithin. Key findings explored include knowledge sharing methods, knowledge transfer plans and the pivotal role of technology in facilitating knowledge transfer in the aviation industry. Additionally, this review assesses the challenges and barriers that organizations encounter in implementing effective knowledge transfer and succession planning practices. By synthesizing and systematically evaluating the existing literature, this review provides valuable insights for aviation industry professionals, researchers, and policymakers, and offers recommendations for enhancing knowledge transfer and succession planning strategies in this dynamic and evolving field.
Keywords: Knowledge management; Aviation industry; Succession planning; Knowledge sharing.